The characteristics of successful benchmarking implementation : guidelines for a national strategy for promoting benchmarking - Abbas, Ahmed (Massey University, 2014)
The MPhil research project presented in this thesis forms the first part of an intended PhD research project. The purpose of the PhD will be to develop a framework to increase the uptake of benchmarking on a national level whilst the aim of the MPhil is to examine the state of benchmarking globally. More specifically, the study objective is to measure and understand the perceived effectiveness, awareness, current and future uptake of benchmarking. The study also explores best practice benchmarking characteristics such as duration of the projects, motivations of benchmarking projects and main benefits of benchmarking. An on-line questionnaire was used to collect data. The questionnaire was translated into five languages and promoted mainly by the Global Benchmarking Network, (GBN) a network of benchmarking centres representing 21 countries. The data was then analysed using SPSS statistical package. The questionnaire consists of seven sections: (1) Organisation’s profile, (2) Use of improvement technique, (3) General questions on benchmarking, (4) Best practice benchmarking projects planning phase, (5) Best practice benchmarking projects research and analysis phase, (6) Best practice benchmarking projects implementation phase, and finally (7) Best practice benchmarking projects evaluation phase. The analysis suggests that informal and performance benchmarking is being used by a majority of organisations while best practice benchmarking is lagging behind them. Benchmarking awareness, effectiveness and future uptake compares favourably with other popular improvement techniques.
Keywords: Benchmarking; Organisational effectiveness